Regulatory long non-coding RNAs in root growth and development. (28th February 2022) - Roulé, Thomas; Crespi, Martin; Blein, Thomas
Abstract : As sessile organisms, plants have evolved sophisticated mechanisms of gene regulation to cope with changing environments. Among them, long non-coding RNAs (lncRNAs) are a class of RNAs regulating gene expression at both transcriptional and post-transcriptional levels. They are highly responsive to environmental cues or developmental processes and are generally involved in fine-tuning plant responses to these signals. Roots, in addition to anchoring the plant to the soil, allow it to absorb the major part of its mineral nutrients and water. Furthermore, roots directly sense environmental constraints such as mineral nutrient availability and abiotic or biotic stresses and dynamically adapt their growth and architecture. Here, we review the role of lncRNAs in the control of root growth and development. In particular, we highlight their action in fine-tuning primary root growth and the development of root lateral organs, such as lateral roots and symbiotic nodules. Lastly, we report their involvement in plant response to stresses and the regulation of nutrient assimilation and homeostasis, two processes leading to the modification of root architecture. LncRNAs could become interesting targets in plant breeding programs to subtly acclimate crops to coming environmental changes.